ANALISIS PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) PADA MASA PANDEMI COVID-19 - Leli Anggraeni; Abdul Wahid Mahsuni; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study aims to explain the effect of ROA, ROE, NPM and EPS on stock prices during the covid-19 pandemic in manufacturing companies listed on the IDX. The data used is secondary data, obtained from the Investment Gallery, Faculty of Economics and Business, Islamic University of Malang and the official website www.idx.co.id. Sampling was done by using a purposive sampling method. The sample in this study were 41 manufacturing banking companies with 3 quarters. So obtained a sample of 123 samples. The results of this study indicate that the variabels ROA, ROE and EPS partially have a positive and significant effect on stock prices. While the NPM partially does not have a significant effect on stock prices.Keyword: ROA, ROE, NPM, EPS, Stock Price